2016
DOI: 10.18632/oncotarget.10574
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from human colorectal cancer induce a tumor-like behavior in colonic mesenchymal stromal cells

Abstract: BackgroundCancer cells, including colorectal cancer ones (CRC), release high amounts of nanovesicles (exosomes), delivering biochemical messages for paracrine or systemic crosstalk. Mesenchymal stromal cells (MSCs) have been shown to play contradicting roles in tumor progression.ResultsCRC exosomes induce in cMSCs: i) atypical morphology, higher proliferation, migration and invasion; ii) formation of spheroids; iii) an acidic extracellular environment associated with iv) a plasma membrane redistribution of vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 54 publications
0
104
0
Order By: Relevance
“…Similar results were obtained from IGROV-1, with cisplatin EVs increasing invasiveness by about 5-fold (p = 0.042) (figure 2B). Various studies have shown that EVs can induce an invasive and motile phenotype in recipient cells (63)(64)(65). Our results suggest that, at least in the case of A2780 and IGROV1 cells, the EVs released under normal conditions cannot induce greater levels of invasion when added to cells.…”
Section: Evs Released By Cisplatin-treated Cells Have the Capacity Tomentioning
confidence: 54%
“…Similar results were obtained from IGROV-1, with cisplatin EVs increasing invasiveness by about 5-fold (p = 0.042) (figure 2B). Various studies have shown that EVs can induce an invasive and motile phenotype in recipient cells (63)(64)(65). Our results suggest that, at least in the case of A2780 and IGROV1 cells, the EVs released under normal conditions cannot induce greater levels of invasion when added to cells.…”
Section: Evs Released By Cisplatin-treated Cells Have the Capacity Tomentioning
confidence: 54%
“…Furthermore, stress hematopoiesis, as known, can take place in ectopic sites in Cooley's anemia leading to facial deformity. MSC supporting activity in tissue specific niches for highly demanded lineages, like the hematopoietic and the intestinal epithelia, might allow permissive cross-lineage colonization, as indicated by their functional deployment by adenocarcinoma cells [19], or BM diffusing neuroblastomas. We could thus speculate that some circulating white hematopoietic precursor might, when necessary, utilize peri-cryptal myofibroblasts, as nurturing pseudo-crypt for a local quick expansion [21].…”
Section: Discussionmentioning
confidence: 99%
“…Also, they suggested that inhibition of tumor exosomes releasing could be a therapeutic way to interfere with tumor growth. 90 EGFRvIII is expressed in a kind of glioblastoma and its expression is detectable in serum exosomes. This finding helps glioblastoma patients to avoid invasive biopsy of the brain tumor, because the diagnosis of EGFR status in the blood sample provides information about the nature of the disease.…”
Section: Tumor-derived Exosomes In Mscsmentioning
confidence: 99%